PHYSICAL ACTIVITY AND COGNITIVE FUNCTION IN AMONG OLDERADULTS AT ANGGREK HEALTH CENTER, MOJOKERTO - Yossa; Amin; Musthika (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Cognitive decline is one of the health problems often experienced by the elderly due to the ageing process, which can affect their ability to remember, concentrate, and maintain independence in daily activities. Physical activity plays an important role in maintaining cognitive function by increasing blood flow to the brain, stimulating neuroplasticity, and slowing down the degenerative process. This study aims to analyse the relationship between physical activity and cognitive function in elderly at Anggrek Health Centre in Japan Village, Sooko District, Mojokerto. This study used a quantitative method with a correlational analytical design and a cross-sectional approach. A total of 73 elderly people were sampled using total sampling technique. Physical activity was measured using the Physical Activity Scale for the Elderly (PASE), while cognitive function was assessed using the Mini Mental State Examination (MMSE). The data were analysed using the Chi-Square test with a significance level of 0.05. The results showed that the majority of elderly people were in the active physical activity category (68.5%) and had normal cognitive function (67.1%). There was a significant relationship between physical activity and cognitive function (p = 0.001), where physically active elderly people tended to have better cognitive function. These findings emphasise the importance of encouraging regular physical activity as a promotional and preventive measure to maintain the cognitive health of elderly people at the community level.